Analisis Pengendalian Kualitas Produk Fatty Alcohol Dengan Menggunakan Metode Statistical Processing Control (SPC) Pada PT Ecogreen Oleochemicals - Dediyanto Kornelius Tarigan; Zefri Azharman (Prosiding, 2019)
PT. Ecogreen Oleochemicals is a company engaged in the field of oleochemicals. The problem faced by the company is related to the products produced by the company, which in reality is always there is a difference with the standard specifications that have been established and damaged that tend to be high. The purpose of this study to analyze the factors causing and types of product damage that occur the better the quality of raw materials used, the better the quality of fatty alcohol produced. The method used in this study using statistical tools contained in Statistical Process Control (SPC) and Statistical Quality Control (SQC) and Fishbone diagram to determine the causal factors. Collecting data by collecting reports relating to production activities in the field. Based on the pareto chart that has been made obtained the highest level of damage is the type of damage due to tearing to the amount of damage 968 bag, then the second highest is the type of damage due to fall 542 bag. Other types of damage is product damage due to overheating as much as 436 bags and other types of damage as much as 99 bags.